High practice variation in risk stratification, baseline oncological staging, and follow-up strategies for T1 colorectal cancers in the Netherlands - Gijsbers, Kim; de Graaf, Wilmar; Moons, Leon M.G.; ter Borg, F.; (on behalf of the Dutch T1 CRC Working Group) (Endoscopy International Open, 2020)
Background and study aims Based on pathology, locally resected T1 colorectal cancer (T1-CRC) can be classified as having low- or high-risk for irradicality and/or lymph node metastasis, the latter requiring adjuvant surgery. Reporting and application of pathological high-risk criteria is likely variable, with inherited variation regarding baseline oncological staging, treatment and surveillance.Methods We assessed practice variation using an online survey among gastroenterologists and surgeons participating in the Dutch T1-CRC Working Group.Results Of the 130 invited physicians, 53 % participated. Regarding high-risk T1-CRC criteria, lymphangio-invasion is used by 100 %, positive or indeterminable margins by 93 %, poor differentiation by 90 %, tumor-free margin ≤ 1 mm by 78 %, tumor budding by 57 % and submucosal invasion > 1000 µm by 47 %. Fifty-two percent of the respondents do not perform baseline staging in locally resected low-risk T1-CRC. In case of unoperated high-risk patients, we recorded 61 different surveillance strategies in 63 participants, using 19 different combinations of diagnostic tests. Endoscopy is used in all schedules. Mean follow-up time is 36 months for endoscopy, 26 months for rectal MRI and 30 months for abdominal CT (all varying 3–60 months).Conclusion We found variable use of pathological high-risk T1-CRC criteria, creating risk for misclassification as low-risk T1-CRC. This has serious implications, as most participants will not proceed to oncological staging in low-risk patients and adjuvant surgery nor radiological surveillance is considered. On the other hand, oncological surveillance in patients with a locally resected high-risk T1-CRC who do not wish adjuvant surgery is highly variable emphasizing the need for a uniform surveillance protocol.